1993
DOI: 10.1111/j.1525-1470.1993.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Elevatum Diutinum Associated with Celiac Disease: Response to a Gluten‐Free Diet

Abstract: An 11-year-old girl with a history of insulin-dependent diabetes mellitus had erythema elevatum diutinum (EED) associated with a celiac disease related to a possible kidney disease. Dapsone did not improve the skin manifestations. However, the lesions disappeared after a gluten-free diet was begun. To our knowledge, this report describes the first case of EED in a patient with celiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Langerhans' cells have also been postulated in the pathogenesis of EED, suggesting that cell‐mediated reactions may play a role . The formation of granulomas advocate T‐cell‐mediated delayed hypersensitivity reactions …”
Section: Dermatopathology and Pathogenesismentioning
confidence: 91%
See 1 more Smart Citation
“…Langerhans' cells have also been postulated in the pathogenesis of EED, suggesting that cell‐mediated reactions may play a role . The formation of granulomas advocate T‐cell‐mediated delayed hypersensitivity reactions …”
Section: Dermatopathology and Pathogenesismentioning
confidence: 91%
“…Where the CD4 count was stated, eight (42%) patients had a CD4 count of less than 200. Seven of the patients described presented with nodular EED . The stimulus for EED could be due to immune‐complex deposition in blood vessels triggered by the HIV infection itself, or other infections acting as antigenic stimuli .…”
Section: Eed and Associationsmentioning
confidence: 99%
“…Hernandez-Cano et al reported the disappearance of EED lesions in a patient with a liver transplantation following a reduction in cyclosporin dosage [12]. However, EED lesions may not respond to dapsone, or if they do, recurrences are quite common [5,11,24,31,39]. It is possible that the marked fibrosis in late lesions may account for the lack of response to dapsone [8].…”
Section: Discussionmentioning
confidence: 90%
“…Other modes of therapy with variable response include clofazimine, chloroquine, niacinamide, tetracycline, steroids, topical betamethazone, flucinolone under occlusion, phenformin, Colchicine and salfapyridine [10,11,13,19,23,34,37,41]. In one case of EED associated with celiac disease, while dapsone did not improve the skin manifestations, the lesions disappeared with a gluten-free diet [31]. In patients with EED associated with HIV infection, adequate antiretroviral therapy in addition to conventional dapsone therapy was used successfully [38].…”
Section: Discussionmentioning
confidence: 94%
“…Behçet's disease is also associated with neutrophil-rich infiltrates of the skin. Aside from IgA paraproteinemia with or without myeloma, myelodysplastic and myeloproliferative diseases, lymphoma and POEMS syndrome, EED is associated with arthralgia and a number of autoimmune and inflammatory disorders such as rheumatoid arthritis [1], ulcerative colitis [2], Crohn's disease [3], relapsing polychondritis [4], type 1 diabetes [5], Wegener's granulomatosis [6], celiac disease [7], myasthenia gravis [8], hyper-IgD syndrome [9] and HIV infection [10]. We found no association of multiple sclerosis with EED.…”
mentioning
confidence: 99%